PHOTOVOLTAIC STATION "HALF-PYRAMID" WITH DOUBLE-SIDED SOLAR PANELS - Savchenko, Natalia; Tretiak, Andrii (Collection of scientific papers «ΛΌГOΣ», 2025)
Solar energy today has the greatest chance of becoming fundamental among the varieties of alternative energy sources against the background of the growth of its share in the world energy balance. This is due to the fact that the source of solar energy is radiation, namely thermonuclear reactions on the Sun, which are inexhaustible. Also, important factors in the rapid development of solar energy are high environmental friendliness and low cost of electricity production.